Managing Change for Competitive Success - Jelinek, Mariann; Pettigrew, Andrew; Whipp, Richard (Academy of Management Review, 1993)
The article reviews the book “Managing Change for Competitive Success,” by Andrew Pettigrew and Richard Whipp.